2001
DOI: 10.1038/sj.onc.1204289
|View full text |Cite
|
Sign up to set email alerts
|

Over-representation of a germline variant in the gene encoding RET co-receptor GFRα-1 but not GFRα-2 or GFRα-3 in cases with sporadic medullary thyroid carcinoma

Abstract: In contrast to the hereditary form of medullary thyroid carcinoma (MTC), little is known about the etiology of sporadic MTC. Somatic gain-of-function mutations in the RET proto-oncogene, encoding a receptor tyrosine kinase, are found in an average of 40% of sporadic MTC. We analysed 31 sporadic MTC for somatic and germline variants in GFRA1, GFRA2 and GFRA3 which encode the co-receptors of RET. Although there were no somatic mutations in any of the three genes, a sequence variant (7193C4G) in the 5'-UTR of GFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…With regard to germline sequence variant in intron 14 (IVS14–24G→A), it has been found to be both associated [69] and unassociated [81] with sporadic MTC. Although GFRα1–193, a polymorphism of the GFR α 1 gene, was found to be associated with sporadic MTC in a small case-control study [82], this result was not confirmed in 2 larger studies [77,83]. …”
Section: Molecular Biology Of Mtc and The Ret Proto-oncogenementioning
confidence: 64%
“…With regard to germline sequence variant in intron 14 (IVS14–24G→A), it has been found to be both associated [69] and unassociated [81] with sporadic MTC. Although GFRα1–193, a polymorphism of the GFR α 1 gene, was found to be associated with sporadic MTC in a small case-control study [82], this result was not confirmed in 2 larger studies [77,83]. …”
Section: Molecular Biology Of Mtc and The Ret Proto-oncogenementioning
confidence: 64%
“…Association studies in sMTC reported negative results, apart from for several RET SNPs (Fugazzola et al 2008, Fernandez et al 2009, for variants in GFRA2 (Gimm et al 2001b, Borrego et al 2002, Cebrian et al 2005, GFRA3 (Gimm et al 2001b, Borrego et al 2002, Cebrian et al 2005, Ruiz-Llorente et al 2007, GFRA4 (Cebrian et al 2005), NTRK2 (Gimm et al 2001a), and NTRK3 (Gimm et al 2001a), among many others, assessed in the study by Ruiz-Llorente et al (2007). Some of these genes should not be completely discarded, however, due to the limited power of some of the studies.…”
Section: Negative Resultsmentioning
confidence: 99%
“…One of them is the GDNF family receptor a 1, which acts as a co-receptor of RET, and is encoded by the GFRA1 gene. The promoter variant rs45568534 (c.K193COG) was first associated with sMTC development in a small group of patients, who also showed a tendency toward a higher expression of tumoral GFRA1 at both the mRNA and the protein levels when carrying the risk alleles (Gimm et al 2001b). This association was not reproduced in larger casecontrol studies (Borrego et al 2002, Cebrian et al 2005, although another variant in the 3 0 UTR (rs1061413, c.*946COG) was significantly associated (Cebrian et al 2005).…”
Section: Ret Polymorphisms In Smtcmentioning
confidence: 99%
“…32 Recently, it has been reported that a -193C to G sequence variant in the 5Ј-untranslated region of GFRA1 was found in 15% of cases with sporadic medullary thyroid cancer, suggesting an association of this variant with carcinogenesis. 33 Despite the limitations of a cross-sectional study, our analyses showed a prominent effect of 3 gene polymorphisms on the risk of developing HCC. Because most HCV-related HCCs arise from a background of cirrhosis, these 3 SNPs might have association with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%